Self-Persuasion: Evidence from Field Experiments at Two International Debating Competitions - Peter Schwardmann; Egon Tripodi; Joël J. van der Weele (Center for Economic Studies and ifo Institute (CESifo), 2019)
Does the wish to convince others lead people to persuade themselves about the moral and factual superiority of their position? We investigate this question in the context of two international debating competitions, where persuasion goals (pro or contra a motion) are randomly assigned to debaters shortly before the debate. Using incentives for truthful reporting, we find evidence of self-persuasion in the form of (i) factual beliefs that become more conveniently aligned with the debater's side of the motion, (ii) shifts in attitudes, reflected in an increased willingness to donate to goal-aligned charities, and (iii) higher confidence in the strength of one's position in the debate. Self-persuasion occurs before the debate and subsequent participation in the open exchange of arguments does not lead to convergence in beliefs and attitudes. Our results lend support to interactionist accounts of cognition and suggest that the desire to persuade is an important driver of opinion formation and political partisanship.
Keywords: 330